Analgesic Effect of Intraarticular Tramadol with Morphine after Arthroscopic Knee Surgery - Faisal, Hussain; Lamichhane, Arjun; Mahara, Deepak (Nepal Orthopaedic Association Journal, 2013)
Introduction: Post-operative improved pain control of patients has made arthroscopy as a day care procedure, reducing patient’s expenses and hospital staffs work load. Various analgesic drugs have been administered into the joint following Arthroscopy. Intra-articular injection of morphine has been practiced in many centres all over the world. We aimed to compare the efficacy of intra-articular tramadol and morphine. Tramadol is an opioid drug with similar analgesic properties like morphine. Tramadol unlike morphine is readily available over the counter not being abused and has more favourable side effects. Methods: It was a prospectively randomized double-blind study in which sixty patients having elective arthroscopic surgery of the knee were randomized into two groups. Group A (Tramadol Group) received intra-articular tramadol 50mg and Group B (Morphine Group) received morphine 5mg in equivalent volumes. Post-operative pain using Visual Analogue Score (VAS) between 0 and 10, (0 no pain to 10 worst pain) requirement of first analgesic, and incidence of side effects were recorded postoperatively at intervals of 3,4,5,6 and 24 hours. Results: The assessment of VAS score among the two groups in 3,4,5,6 and 24 hours of IA injection showed a p value of 0.349, 0.807, 0.676, 0.271 and 0.163 respectively, suggesting non significant difference in two groups. There was statistically significant result (p=0.005) for request of first analgesia (Ibuprofen 400mg+ Paracetalmol 500mg) at 6 hours of IA injection with tramadol group, requiring less analgesics. There are no other clinically important differences between the groups, including preoperative duration of symptoms, postoperative pain scores and side effects irrespective of the diagnosis and the procedure performed. Conclusion: 50 mg IA tramadol provides analgesia equivalent to 5 mg IA morphine. DOI: http://dx.doi.org/10.3126/noaj.v3i1.9320 Nepal Orthopedic Association Journal 2013 Vol.3(1): 14-18